(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Wireless Sensor Network applications are pulling in more research, particularly in energy saving techniques that are the centre purpose of analysts here. One of the fascinating and helpful uses of Wireless Sensor Networks is the movable target tracking. Wireless Sensor Networks is utilized to track movable target in a monitored territory and to report its location to the base station. .Identification of exact position and path travelled by the movable target over an area is a noteworthy energy customer procedure inside of Wireless Sensor Networks. In this paper, we consider a best design requirements to outline energy efficient cluster based routing protocol for Target Tracking in Wireless Sensor Networks (WSNs), with the assistance of this convention expand network lifetime of each nodeb and decrease communication cost between nodes. Specifically, we deliberately outline a energy efficient target tracking protocol with thought of couple of imperative parameters, such as, aggregate remaining energy. At last, we abridge and finish up the paper with some future headings.